Doubling Farmers Income in India-Possibilities and Challenges - N. , Sujatha (Journal of Agricultural Extension Management, 2022)
The contribution of agriculture and allied sectors to GDP and GVA has been declined, but still remaining an important sector because of its contributed role in employment, providing raw materials to Agri based industries, in national food security and rural livelihood. As high as 70 percent of rural households still depends primarily on agriculture for their livelihood and getting subsistence level of incomes, some of farmers committed suicide. There are many reasons for lesser income in agriculture sector. Hence the central government aim to double farmers income by 2022-23 is central to promote farmers welfare and income. The central government has constituted the Dalwai Committee in April 2016 to recommend measures required to fulfil the target after Prime Minister Narendra Modi announced to double farmer’s income in six years. In budget 2020-2021, Government provides 30% higher budget allocation for agriculture.in 2021-22 budget The ministry has been allocated Rs.1,31,531 Crore. The present study going to analyses the possibilities and challenger of doubling farmers income by 2022-23